2007
DOI: 10.1118/1.2804616
|View full text |Cite
|
Sign up to set email alerts
|

Fast, high‐resolution 3D dosimetry utilizing a novel optical‐CT scanner incorporating tertiary telecentric collimation

Abstract: This study introduces a charge coupled device (CCD) area detector based optical-computed tomography (optical-CT) scanner for comprehensive verification of radiation dose distributions recorded in nonscattering radiochromic dosimeters. Defining characteristics include: (i) a very fast scanning time of ~5 min to acquire a complete three-dimensional (3D) dataset, (ii) improved image formation through the use of custom telecentric optics, which ensures accurate projection images and minimizes artifacts from scatte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 49 publications
3
59
0
Order By: Relevance
“…In theory, artifacts caused by the scattered light in optical CT scanners using a single laser source can be eliminated by reducing the detector apertures. In CCD-based optical CT scanners, telecentric lens can be used to select parallel beams from the scanned dosimeters (Krstajic and Doran, 2006;Sakhalkar and Oldham, 2008), thus minimizing the collection of the scattered light in the camera apertures.…”
Section: Light Scattering In Optical Ctmentioning
confidence: 99%
See 1 more Smart Citation
“…In theory, artifacts caused by the scattered light in optical CT scanners using a single laser source can be eliminated by reducing the detector apertures. In CCD-based optical CT scanners, telecentric lens can be used to select parallel beams from the scanned dosimeters (Krstajic and Doran, 2006;Sakhalkar and Oldham, 2008), thus minimizing the collection of the scattered light in the camera apertures.…”
Section: Light Scattering In Optical Ctmentioning
confidence: 99%
“…The idea of optical CT was first introduced to gel dosimetry in 1996 together with a new tissue equivalent polymer gel dosimeter . Since then, optical CT scanners in a variety of forms have been built for imaging gel phantoms irradiated with photon, electron, proton beams as well as brachytherapy radiation sources (Islam et al, 2003;Wuu et al, 2003;Oldham and Kim, 2004;Xu et al, 2004;Doran et al, 2006;DeJean et al, 2006;Krstajic and Doran, 2006;Sakhalkar and Oldham, 2008;Olding et al, 2010). Currently, the advantage of the optical CT approach over other dose readout methods for gel dosimetry is commonly acknowledged (Oldham et al, 2001;Lopatiuk-Tirpak et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…We note that there were a few successful attempts to use telecentric lenses for optical computed and emission tomography. [7][8][9] However, the advantage of telecentric lenses for imaging highly anisotropic scattering medium, specifically biological tissue had not yet been explored systemically. Recently, we have proven the advantages of using telecentric lens for imaging through highly scattering media such as biological tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies presented that PRESAGE ® /Optical CT system had excellent precision, accuracy, reproducibility and robustness 3D dosimetry. [13][14] Recently, it is reported that ferrous xylenol-orange gel/optical-CT dosimetry system were used to demonstrate the feasibility of three dimensional dosimetry in RPC head and neck phantom. 15 Previous work has focused on the fundamental dosimetric characteristics of PRESAGE ® and investigation of the feasibility of the PRESAGE ® /optical CT system for 3D dosimetry.…”
Section: Introductionmentioning
confidence: 99%